THE USE OF PREWRITING METHODS TO DEVELOP EFL STUDENTS’ COMPETENCE IN WRITING - Magdahalena tjalla (ETERNAL (English, Teaching, Learning and Research Journal), 2016)
The process approach becomes a choice for teachers to apply in the writing class rooms since this approach focuses on the connection of the writing topics to the students’ experiences which makes the writing tasks meaningful to students (Yan, 20014).  In process approach, students’ composition is a product that should go through several stages: prewriting, writing, and post writing. In prewriting, there are several interesting  activities that can be done in to improve students’ writing skill: asking questions, discussing an interesting topic, taking notes, free writing, clustering, brainstorming,  grouping, doing buzy group, outlining, completing notes based on pictures,  making a list, making idea map, categorizing,  and classifying (Oshima and Hogue, 1997;  Harmer, 2004, Huizenga, et al.,1990). Some research have proved the significant role of process writing to improve students’ skill in writing, Ho (2006) conducted a research on the effectiveness of using process approach in writing to primary school students of upper level and lower level through pre and post test, questionnaire, interview, and observation and found that process writing was able to develop  the writing abilities and students’ attitude towards writing in all levels of students.  Hasan & Akhand (2010)  in their research combine the product approach and the process approach to teach ESL students in Bangladesh and revealed that the combination of the two approaches facilitate students to do writing tasks.  Badger and White (2000) in Yan (2014) combine the process approach and the genre approach which he called process genre approach in their study and  reported that this approach  helped  students  study the relationship between purpose and form for a particular genre while they follow the stages in process writing:  prewriting, drafting, revising, and editing. Using these steps develops students’ awareness of different text types and of the composing process.